??????? ??? ????? ????? ?????? ?????? ??? ?????? ???? ????? ?? ??????? ???????? ????? ?????? ???? ??? ????? The Relationship of Self-Concept Profile and Speaking Skill Proficiency on the First-Grade Female Student in Secondary School at Imam Muslim Sei Rampah - Anisa Maulidya (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
Abstract: This study aims to know the self-concept profile and speaking skill proficiency and a relationship between both of them on the first-grade female students in secondary school at Imam Muslim Sei Rampah. The research methodology used is a quantitative correlational method using statistical data with the Spearman rank formula to obtain the research results. The result of this research is known the level of self-concept among the first-grade female students in secondary school at Imam Muslim Sei Rampah is classified as good, with a percentage of 43%, which means 13 students. The level of speaking skill proficiency among first-grade female students in secondary school at Imam Muslim Sei Rampah is classified as good, with a percentage of 50%, which means 15 students. There is a significant positive relationship between self-concept and speaking skill proficiency among the first-grade female students in secondary school at Imam Muslim Sei Rampah, with a correlation coefficient of 0.693, representing 69%, indicating a moderate and positive correlation. Key words: Self-Concept, Speaking Skill, Arabic Speaking Skills. ?????? ?????: ???? ??? ????? ?????? ???? ????? ????? ????? ??? ????? ?????? ?????? ?????? ??? ?????? ???? ????? ?? ??????? ???????? ????? ?????? ???? ??? ?????. ??????? ??????? ?????? ?????? ????? ?????? ??????? ?? ????? ????? ???????? ????????? ?????? ????? (spearman rank) . ?????? ????? ??? ??? ?? ????? ????? ??????? ???? ????? ?? ??????? ???????? ????? ?????? ???? ??? ????? ?? ??? ??? ??????? 43% ???? 13 ?????? ????? ????? ?????? ????? ?? ??? ??? ??????? 50% ???? 15 ?????? ?????? ??? ????? ????? ?????? ?????? ????? ????? ???????? 0,693 ??????? 69% ???????? ?????? ?????? ??????. ??????? ???????? : ????? ?????? ????? ??????? ????? ?????? ?????? ???????.